Overview of the CLEF-2005 Cross-Language Speech Retrieval Track - White, Ryen W.; Oard, Douglas W.; Jones, Gareth J. F.; Soergel, Dagobert; Huang, Xiaoli (Cross-Language Evaluation Forum (CLEF 2005), Vienna, Austria, 2005)
The task for the CLEF-2005 cross-language speech retrieval track was to identify topically coherent segments of English interviews in a known-boundary condition. Seven teams participated, performing both monolingual and cross-language searches of ASR transcripts, automatically generated metadata, and manually generated metadata. Results indicate that monolingual search technology is sufficiently accurate to be useful for some purposes (the best mean average precision was 0.18) and cross-language searching yielded results typical of those seen in other applications (with the best systems approximating monolingual mean average precision).